THE EFFECT OF FOOT EXERCISE ON LOWER EXTREMITY SENSORY NEUROPATHY STATUS AND BLOOD GLUCOSE LEVELS PATIENTS TYPE 2 DIABETES MELLITUS - Setiawan Rosyid, Leili; Ana Angraini, Novita (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. The increasing prevalence of type 2 diabetes mellitus in developed and developing countries has become a global health problem or disease in society. Therefore, Type 2 Diabetes Mellitus can be prevented with regular exercise, healthy and regular life. The purpose of this study was to determine the effect of foot exercise on the status of lower extremity sensory neuropathy and changes in blood glucose levels in patients with type 2 diabetes mellitus at Tanjunganom Public Health Center, Nganjuk Regency. Method. The design in this study was pre-experimental with a one group pre-posttest design approach, this study sought the effect of foot exercise on the status of lower extremity sensory neuropathy and changes in blood glucose levels in patients with type 2 diabetes mellitus at Tanjunganom Public Health Center, Nganjuk Regency, in this study involved 30 respondents with purposive sampling technique. This research was conducted on October 14-21, 2022. Result&Analysis. From the results of the Wilcoxon test, it was found that after doing foot exercises, the sensory neuropathy status of the lower extremities in the right extremity was obtained value = 0.000<0.05, besides that after doing leg exercises, changes in blood glucose levels were obtained value = 0.000<0.05 this indicates that there was an effect of foot exercise on the sensory neuropathy status of the lower extremities and changes in blood glucose levels in people with diabetes mellitus 2. Discussion. Patients with type 2 Diabetes Mellitus  can applicate foot exercises to change lower extremity sensory status and blood glucose level.